Intelligent systems for information processing from representation to applications - Bouchon-Meunier, B. (Bernadette), 1948-; Foulloy, L.; Yager, Ronald R., 1941-; International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems Annecy, France) (Amsterdam ; Boston : Elsevier, 2003)
Intelligent systems are required to enhance the capacities being made available to us by the internet and other computer based technologies. The theory necessary to help providing solutions to difficult problems in the construction of intelligent systems are discussed. In particular, attention is paid to situations in which the available information and data may be imprecise, uncertain, incomplete or of a linguistic nature. Various methodologies to manage such information are discussed. Among these are the probabilistic, possibilistic, fuzzy, logical, evidential and network-based frameworks. One purpose of the book is not to consider these methodologies separately, but rather to consider how they can be used cooperatively to better represent the multiplicity of modes of information. Topics in the book include representation of imperfect knowledge, fundamental issues in uncertainty, reasoning, information retrieval, learning and mining, as well as various applications. Key Features: Tools for construction of intelligent systems; Contributions by world leading experts; Fundamental issues and applications; New technologies for web searching; Methods for modeling uncertain information; Future directions in web technologies; Transversal to methods and domains.
Toward a perception-based theory of probabilistic reasoning with imprecise probabilities / Lotfi A. Zadeh -- Rough set uncertainty in an object oriented data model / Theresa Beaubouef and Frederick E. Petry -- On the representation of fuzzy spatial relations in robot maps / Isabelle Bloch and Alessandro Saffiotti -- Fuzzy "between" operators in the framework of fuzzy orderings / Ulrich Bodenhofer -- A step towards conceptually improving Takagi-Sugeno's approximation / S. Guadarrama, E. Trillas, J. Gutiβerrez and F. Fernβandez -- Combining heterogeneous information in group decision making / F. Herrera, E. Herrera-Viedma, L. Martβinez and P.J. Sβanche -- Function approximation by fuzzy rough sets / Masahiro Inuiguchi and Tetsuzo Tanino -- Query aggregation reflecting domain-knowledge / Troels Andreasen -- Modelling of fuzzy and uncertain spatio-temporal information in databases : a constraint-based approach / G. de Trβe, R. de Caluwe, A. Hallez and J. Verstraete -- A general framework for meta-search based on query-weighting and numerical aggregation operators / Mario Gβomez and Chema Abβasolo -- On the comparison of aggregates over fuzzy sets / Patrick Bosc, Olivier Pivert and Ludovic Liβetard -- Towards an intelligent text categorization for web resources : an implementation / Sławomir Zadroηzny, Klaudia Ławcewicz and Janusz Kacprzyk -- Prototype based reasoning and fuzzy modeling / Ronald R. Yager -- Gradual handling of contradiction in argumentation frameworks / C. Cayrol and M.C. Lagasquie -- Coherent conditional probability as a tool for default reasoning / Guilianella Coletti, Romano Scozzafava and Barbara Vantaggi -- Detecting conflict-free assumption-based knowledge bases / Rolf Haenni -- Theory of belief functions : history and prospects / A.P. Dempster -- Towards another logical interpretation of Theory of evidence and a new combination rule / Laurence Cholvy -- Uncertainty, type-2 fuzzy sets, and footprints of uncertainty / Jerry M. Mendel -- Rough sets, Bayes' theorem and flow graphs / Zdzisław Pawlak -- Belief revision as combinatorial optimization / Arthur Ramer -- Showing why measures of quantified beliefs are belief functions / Philippe Smets -- Extension of coherent lower previsions to unbounded random variables / Matthias C.M. Troffaes and Gert de Cooman -- Clustering of proximity data using belief functions / Thierry Denœux and Mylαene Masson -- A hierarchical linguistic clustering algorithm for prototype induction / I. Gonzβalez Rodrβiguez, J. Lawry and J.F. Baldwin -- A multiobjective genetic algorithm for feature selection and data base learning in fuzzy-rule based classification systems / O. Cordβon, F. Herrera, M.J. del Jesus, L. Magdalena, A.M. Sβanchez and P. Villar -- Mining implication-based fuzzy association rules in databases / Eyke Hθullermeier and Jθurgen Beringer -- Learning graphical models by extending optimal spanning trees / Christian Borgelt and Rudolf Kruse -- Clustering belief functions based on attracting and conflicting metalevel evidence / Johan Schubert -- Models and submodels of fuzzy theories / Vilβem Novβak -- Numerical representations of fuzzy relational systems / Sergei Ovchinnikov -- Normal forms for fuzzy relations and their contribution to universal approximation / Irina Perfilieva -- Associative operators based on t-norms and t-conorms / M. Mas, R. Mesiar, M. Monserrat and J. Torrens -- Non-analytical approaches to model-based fault detection and isolation / Paul M. Frank -- A hybrid fuzzy-fractal approach for time series analysis and prediction and its applications to plant monitoring / Oscar Castillo and Patricia Melin -- Linguistic modeling of physical task characteristics / Sofia Visa, Anca Ralescu, Simon Yeung and Ash Genaidy -- Validation of diagnostic models using graphical belief networks / Oscar Kipersztok and Haiqin Wang -- Adjustment of parallel queuing processes by multi-agent control / Rainer Palm and Thomas A. Runkler -- Is she gonna like it? : automated inspection system using fuzzy aggregation / A. Soria-Frisch, M. Kθoppen and Th. Sy.
Includes bibliographical references and index.
Keywords: Expert systems (Computer science) -- Congresses; Uncertainty (Information theory) -- Congresses; Artificial intelligence -- Congresses; Electronic books; Conference proceedings